SAKRALISASI TARI ANDIR PADA UPACARA PUJAWALI PURA SAREN GONG DI DESA TISTA KECAMATAN KERAMBITAN KABUPATEN TABANAN - Ni Kadek Nia Ciptariani (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
The structure of the Andir dance performance is the result of pouring out ideas, concepts, values and norms held by the local community through sacralization activities by synergizing the Andir dance and Rangda Sungsungan which produces the sacred Andir dance. The structure of the Andir dance can be seen from the context of its emergence and development, the cultural context of the community, and the context of the performance which is the result of the evolution of the dance, which relies on both internal and external energy forces. The cultural conceptions of society, which are largely oriented towards complementary dualism, are applied to the Andir dance. Andir dance, which previously (from 1928) was a secular dance, later became a sacred art (from 1994 until now) involving sacred objects (rangda sungsungan), ritual ceremonies, sacred places, purified performers, and time that is considered sacred. The involvement of these elements makes the Andir dance a sacred palace Legong dance whose sacredness originates from the Rangda Sungsungan.